"O fascismo ainda está cá dentro", ou a escrita como combate em A máquina de fazer espanhóis, de Valter Hugo Mãe. - Figueiredo, Annie Tarsis Morais (2016)
This dissertation studies the writing of character-narrator Mr. Silva, and the battle fought against the fascist ways within us and in the world. Discussing contemporaneity and biopolitics (Negri, 2001; Agamben, 2002; Safatle, 2015) through Portuguese author valter hugo mãe's a máquina de fazer espanhóis (2011) demands an understanding of the space occupied by the elderly (Debert, 1999; Navarro-Swain, 2003; Brum, 2010), as well as the Portugueses' lieu (Lourenço, 2001; Reis, 2004) in the current sociopolitical conjecture. The writing is marked by a plurality of discourses about the past Salazar era, about old age, and about the current status of things in what is still called democracy. Biopotency is creation, the concrete transformation of a possibility in the midst of life's expiration and confinement. Thus, Mr. Silva's writing presents the condition of those seen as abject, who live in the ―social backstages‖, spaces reserved to them because of the individualization model connected to the specific life forms produced by the norm and power systems. Hence, the hypothesis is that all this writing/production/fabrication of an old man confined in an asylum becomes a criticism and an alert about fascist ways, also pointing its opposite, which is the profound relationship with the other, and the transformation of a war machine (Deleuze, 1997) into a revolutionary imperative constituted by life potency, which in this case is the writing. This way, a time collectively shared is taken as a counterpoint to the banality of the hate for one another.